Finite element simulation of deformation behavior of prefabricated holes in ultra-heavy plates by gradient temperature rolling - H. Fu (Metalurgija, 2020)
Based on the Deform-3D finite element simulation software, the numerical analysis of prefabricated holes in the core of ultra-heavy plates is carried out in different rolling schemes. In this paper, the deformation of the hole in core under uniform temperature rolling (UTR) is compared by different gradient temperature rolling (GTR) processes. The results show that the GTR can improve the core deformation compared with the UTR. The increase of the number of water cooling can accelerate the welding of the core holes and the healing of the final gap, and multi-pass watercooled GTR should be used for ultra-heavy plate rolling.